The roles of omega-3 fatty acids and resolvins in allergic conjunctivitis. Issue 5 (October 2019) - Hirakata, Toshiaki; Yokomizo, Takehiko; Matsuda, Akira
Abstract : Purpose of review: Lipids are one of the most important constituents in our body. Advances of lipidomics are elucidating the new roles of various lipid molecules in allergic diseases. For example, some reports showed anti-inflammatory effects of omega-3 fatty acids (FAs), such as docosahexaenoic acid, eicosapentaenoic acid, and their metabolites, on allergic diseases. Here, we introduce the role of lipid mediators in allergic conjunctivitis mouse model. Recent findings: Lipidomics using liquid chromatography–tandem mass spectrometry can profile numerous lipid molecules from small tissue samples such as conjunctival specimens. Lipidomics analysis showed that various inflammatory lipid mediators are produced in the conjunctival tissue of allergic conjunctivitis mouse model. Dietary omega-3 FAs reduced these inflammatory lipid mediators in the conjunctiva and alleviated allergic conjunctivitis symptoms in mouse models. In addition, the roles of specialized proresolving lipid mediators (SPMs) have been reported for allergic inflammation. Summary: Lipid mediators have important roles for the pathophysiology of the allergic diseases including allergic conjunctivitis. Omega-3 FAs and SPMs are expected as new treatment tools for allergic conjunctivitis.